2014
DOI: 10.1371/journal.pone.0100894
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol-Induced Effects on Sting Extension Response and Punishment Learning in the Western Honey Bee (Apis mellifera)

Abstract: Acute ethanol administration is associated with sedation and analgesia as well as behavioral disinhibition and memory loss but the mechanisms underlying these effects remain to be elucidated. During the past decade, insects have emerged as important model systems to understand the neural and genetic bases of alcohol effects. However, novel assays to assess ethanol's effects on complex behaviors in social or isolated contexts are necessary. Here we used the honey bee as an especially relevant model system since… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
40
0
3

Year Published

2015
2015
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 74 publications
5
40
0
3
Order By: Relevance
“…Pszczoły okazały się doskonałym obiektem do badań społecznych aspektów spożywania alkoholu ze względu na to, że są zwierzętami mającymi zdolność porozumiewania się i uczenia, a zmiany w ich skomplikowanym behawiorze są łatwe do zauważenia (9). Ponadto pszczeli model do badania alkoholizmu jest szczególnie istotny, ponieważ owady te mają kontakt z naturalnymi źródłami alkoholu w naturze w postaci sfermentowanego nektaru lub soków roślinnych (41,101). Potwierdzono, że alkohol negatywnie wpływa na pszczoły -"pijące" robotnice są niezdolne do pracy, nie uczą się, poruszają się w sposób nieskoordynowany, a zbieraczki nie wracają do ula po wylocie w celu zdobycia pokarmu (7).…”
Section: Pszczoły Jako Model Do Badania Wpływu Używekunclassified
See 1 more Smart Citation
“…Pszczoły okazały się doskonałym obiektem do badań społecznych aspektów spożywania alkoholu ze względu na to, że są zwierzętami mającymi zdolność porozumiewania się i uczenia, a zmiany w ich skomplikowanym behawiorze są łatwe do zauważenia (9). Ponadto pszczeli model do badania alkoholizmu jest szczególnie istotny, ponieważ owady te mają kontakt z naturalnymi źródłami alkoholu w naturze w postaci sfermentowanego nektaru lub soków roślinnych (41,101). Potwierdzono, że alkohol negatywnie wpływa na pszczoły -"pijące" robotnice są niezdolne do pracy, nie uczą się, poruszają się w sposób nieskoordynowany, a zbieraczki nie wracają do ula po wylocie w celu zdobycia pokarmu (7).…”
Section: Pszczoły Jako Model Do Badania Wpływu Używekunclassified
“…Spożywanie alkoholu powoduje przesunięcie granicy progu wrażliwości na bodźce (Sting Extinsion Response (SER)) -co może wskazywać na działanie przeciwbólowe. Upojenie alkoholowe pszczół wywołuje brak zahamowań w zachowaniu, zakłóca kontrolę nad żądleniem oraz kojarzenie znaczenia bodźców pochodzących ze środowiska (41). Ponadto zachowania higieniczne całej rodziny również ulegają zakłóceniu (9).…”
Section: Pszczoły Jako Model Do Badania Wpływu Używekunclassified
“…Several studies have established that honey bees will willingly consume EtOH solutions that contain sucrose, even at levels of EtOH >10%. These studies have included bees that were restrained and fed specific doses (e.g., see Abramson et al., ; Giannoni‐Guzman et al., ; Maze et al., ; Mustard et al., ) or free flying bees that were trained to a feeder, which was then swapped out for one containing EtOH (Bozic et al., ; Sokolowski et al., ). However, whether or not honey bees prefer to consume EtOH using a 2‐feeder choice assay similar to that used to measure preference in rodent and Drosophila models has not yet been determined.…”
mentioning
confidence: 99%
“…This would be similar to comparing bees treated orally with ethanol and control group bees. For these two groups, both in appetitive and aversive learning tasks the 10% or higher ethanol treatment group performed poorly (Giannoni-Guzmán et al, 2014). However, in a supplemental study we demonstrated in an aversive learning paradigm, ESA conditioning, both A.m. syriaca and A.m. caucasica demonstrated complete reversal of punishment learning.…”
Section: Appetitive Vs Aversive Learningmentioning
confidence: 67%
“…We used a shuttle box apparatus as described before (Agarwal et al, 2011;Giannoni-Guzmán et al, 2014). The shuttle box measured 15 cm long by 2 cm wide and contained an electric shock grid with wires spaced .35 cm apart.…”
Section: Supplemental Electric Shock Avoidance Assay (Esa)mentioning
confidence: 99%